Buenas prácticas docentes desde la perspectiva de los estudiantes de la Universidad Santo Tomás – Tunja (2021)
Most of the investigations on educational research about teaching practices are based on classroom observations and interviews to the teachers about their methodologies. However, students can make important contributions into this field given that their "acadimi sense" (jackson, 2002) allows them to value the pedagogical quality of their teachers. This article follows a qualitative research that adopts an interpretative approach which is aimed at inquiring into the good teaching practices at Universidad Santo Tomás – seccional Tunja (USTA Tunja) from the viewpoint of the students. In this project, the good teaching practices, framed within the new agenda for didactics, are made up of different academic, professional, and moral aspects, among others. In this research project, the good teaching practices are unearthed through semi-structured questionnaires. In this way, the complexities of the experiences and individual subjectivities are perceived in order to explore the teaching practices at the University and contribute to the teachers’ professional development.